2012
DOI: 10.1590/s0103-90162012000200001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing biophysical variable parameters of bean crop with hyperspectral measurements

Abstract: Recently high spectral resolution sensors have been developed, which allow new and more advanced applications in agriculture. Motivated by the increasing importance of hyperspectral remote sensing data, the need for research is important to define optimal wavebands to estimate biophysical parameters of crop. The use of narrow band vegetation indices (VI) derived from hyperspectral measurements acquired by a field spectrometer was evaluated to estimate bean (Phaseolus vulgaris L.) grain yield, plant height and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 23 publications
(36 reference statements)
3
16
0
6
Order By: Relevance
“…The result obtained here agrees with that of Monteiro et al (2012), who observed the same behavior in this parameter for irrigated beans, increasing from 8.73 to 17.05 pods plant -1 with water depths of 179.5 and 357.5 mm, and decreasing to 12.63 pods as the water depth increased to 406.2 mm. Torres et al (2013) observed that the number of pods per plant was highest with the replacement of 100% ETc, 10.37 pods per plant, for the cultivar Pérola, studying different replacement levels and different soil covers.…”
Section: A Bw Cw Py W Pwsupporting
confidence: 92%
“…The result obtained here agrees with that of Monteiro et al (2012), who observed the same behavior in this parameter for irrigated beans, increasing from 8.73 to 17.05 pods plant -1 with water depths of 179.5 and 357.5 mm, and decreasing to 12.63 pods as the water depth increased to 406.2 mm. Torres et al (2013) observed that the number of pods per plant was highest with the replacement of 100% ETc, 10.37 pods per plant, for the cultivar Pérola, studying different replacement levels and different soil covers.…”
Section: A Bw Cw Py W Pwsupporting
confidence: 92%
“…The higher shoot dry matter (Table 1) (Jensen, 2009;Monteiro et al, 2012;Ponzoni et al, 2012). The vegetation activity includes leaf area index (LAI), green coverage, chlorophyll content, green biomass, Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the red and near infrared bands are widely used to calculate vegetation indices because they are the most well correlated with green biomass. Monteiro et al (2012) correlated the LAI with hyperspectral data in a bean crop and reported negative correlations between the LAI and the bands at the visible wavelengths, and positive bands at the near infrared wavelengths.…”
Section: Resultsmentioning
confidence: 99%
“…Para esta variável, o modelo que melhor se ajustou aos índices de vegetação foi o geométrico. Monteiro et al (2012) …”
Section: Resultsunclassified
“…Para estimar o IAF, as medidas de radiação difusa, acima e abaixo do dossel do feijão, foram coletadas no início da manhã em 01/11/2007, em todas as parcelas, no estádio fenológico R6 (floração), conforme Gepts & Fernandéz (1982). O estádio R6 foi caracterizado como o melhor estádio da cultura para estimar as variáveis biofísicas, por apresentar a maior quantidade de biomassa verde das plantas (Monteiro et al, 2012).…”
Section: Methodsunclassified